ENHANCING ISOLATED GRAMMAR TEACHING THROUGH TRANSLATION: SENTENCE LEVEL AND BEYOND - Murtisari, Elisabet Titik (LLT Journal: A Journal on Language and Language Teaching, 2020)
Associated with grammar-translation method, translation is still often seen as a mere replacement of linguistic forms, which is a far cry from its nature as an act of communication. On the other hand, while being criticized for not assisting learners enough to use grammar in a communication context, isolated grammar teaching has its own merits and is still widely practiced. By implementing translation for meaning-making, this action research seeks to examine how translation may be integrated into the traditional grammar teaching to assist tertiary EFL students to learn L2 forms in communicative contexts. With translation employed at the sentence and discourse levels after the practice session, it was revealed through the participants reflections that translation exercises may further consolidate students knowledge of how to use specific forms in various contexts, especially as it relates to lexico-grammatical aspects, help deal with L1 interferences, and are an effective way to raise students awareness of the essential role of grammar in meaning-making.